Polymer material with nuclear radiation protection function

By introducing ultra-high molecular weight polyethylene, modified nano samarium oxide and tungsten boride into polyvinyl materials, the problem of insufficient performance of polyvinyl materials is solved, and its shielding ability and flame retardancy to nuclear radiation is significantly improved. A stable nuclear radiation protection effect has been achieved.

CN119286097APending Publication Date: 2025-01-10ANHUI YINGLIU JIUYUAN NUCLEAR ENERGY NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411549480.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing polyvinyl nuclear radiation protection materials have low flame retardant, oxidation and mechanical properties, making it difficult to meet the higher demand in the technical field of nuclear radiation protection materials.

Method used

The ultra-high molecular weight polyethylene, modified nano samarium oxide and tungsten boride are used for melt blending to prepare polymer materials with nuclear radiation protection function. By modifying nano samarium oxide, the shielding performance and flame retardancy of the modified nano samarium oxide enhancement material. Improve its protection against radiation such as neutrons, gamma rays and photons.

Benefits of technology

It significantly improves the shielding performance, flame retardancy and oxidation resistance of the material, provides stable nuclear radiation protection, and maintains good performance at high temperatures, which has important application value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005114686250000031
    Figure BDA0005114686250000031
  • Figure BDA0005114686250000041
    Figure BDA0005114686250000041
  • Figure BDA0005114686250000042
    Figure BDA0005114686250000042
Patent Text Reader

Abstract

The invention discloses a polymer material with a nuclear radiation protection function, and belongs to the technical field of nuclear radiation protection materials. Comprising the following raw materials in parts by weight: 80-100 parts of ultra-high molecular weight polyethylene, 15-25 parts of modified nano samarium oxide, 10-18 parts of tungsten boride and 4-6 parts of a lubricant. The prepared polymer material takes ultra-high molecular weight polyethylene as a matrix, so that the material is endowed with a shielding effect and mechanical strength on neutrons; wherein tungsten boride can further improve the shielding capability of the material to neutrons and also improve the shielding capability of the material to gamma rays; wherein the modified nano samarium oxide has good compatibility with a matrix, can enhance the shielding capability of the material, can also enhance the flame retardance and oxidation resistance of the material, and is stable in performance; therefore, the prepared polymer material is high in shielding performance, has a good protection effect on nuclear radiation, has stable and efficient flame retardance and oxidation resistance, and has important application value in the technical field of nuclear radiation protection materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nuclear radiation protection materials, and in particular relates to a polymer material with nuclear radiation protection function. Background Art

[0002] With the increasing demand for energy and the emphasis on the environment, new energy is developing rapidly. Nuclear energy, as a clean and efficient form of energy, has received widespread attention. However, while using nuclear energy, nuclear reactors will produce extremely radioactive rays. These rays have high energy and strong penetrating power, which are very harmful to the human body and the environment. After a certain dose of thermal neutrons and gamma rays, the human body may experience symptoms such as dizziness, headache, loss of appetite, and even serious damage to organs such as the stomach and gonads; at the same time, strong radiation may damage human DNA, induce cell cancer, and have genetic effects. Therefore, it is necessary to use nuclear radiation protection materials to shield these radioactive substances.

[0003] Existing mature nuclear radiation protection materials include heavy metal shielding materials, metal-based shielding materials and polymer-based shielding materials. Among them, metal-based composite materials are usually based on heavy metals and their oxides, and can be used for neutron shielding in extreme temperature and chemical environments. The characteristic of polymer-based composite materials is that they have a low density and are often used for neutron shielding in spacecraft and portable instruments, but their performance in shielding photons and heavy ions is poor, so heavy metal particles are usually mixed into them to improve their performance in shielding photons and heavy ions.

[0004] Commonly used polymer-based shielding materials include lead boron polyethylene, tungsten boron polyethylene, etc. This type of material mostly contains polyethylene components. Due to its high hydrogen content, mature processing technology, low cost, large elastic scattering cross section, light weight, and good chemical stability, it is widely used as the matrix of radiation shielding composite materials. However, polyethylene-based shielding materials use polyethylene as the matrix, and polyethylene itself has relatively low flame retardant, antioxidant and mechanical properties. Therefore, it is urgent to improve the performance of polyethylene-based shielding materials to meet its higher demands in the field of nuclear radiation protection material technology. Summary of the invention

[0005] The purpose of the present invention is to overcome the defects of the prior art and provide a polymer material with nuclear radiation protection function.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A polymer material with nuclear radiation protection function is prepared by the following steps:

[0008] Ultra-high molecular weight polyethylene, modified nano samarium oxide, tungsten boride and lubricant are added to a mixer and stirred for 30 minutes, and then added to a twin-screw extruder, melt-blended and extruded to obtain a polymer material with nuclear radiation protection function.

[0009] Furthermore, the raw materials are calculated in parts by weight as follows: 80-100 parts of ultra-high molecular weight polyethylene, 15-25 parts of modified nano samarium oxide, 10-18 parts of tungsten boride, and 4-6 parts of lubricant.

[0010] Furthermore, the lubricant is one of magnesium stearate, zinc stearate and paraffin.

[0011] With polyethylene as the matrix, the elastic scattering of C and H elements in polyethylene can slow down neutrons, giving the material a shielding effect on neutrons. In addition, polyethylene has an ultra-high molecular weight, and its mechanical strength and radiation resistance are better than ordinary polyethylene. Not only that, the introduced tungsten boride contains two elements, tungsten and boron, of which high-energy neutrons can be slowed down. Boron has a higher capture cross-section for low-energy neutrons, and has good shielding capabilities for thermal neutrons, fast neutrons, and high-energy neutrons, and can also effectively shield gamma rays.

[0012] Furthermore, the modified nano samarium oxide is prepared by the following steps:

[0013] S1. In a three-necked flask equipped with a stirring device, 3,5-di-tert-butyl-4-hydroxybenzaldehyde, piperidine (condensing agent) and toluene were mixed, the temperature was raised to 35°C, stirred until the solid was completely dissolved, melamine was added, the reaction temperature was controlled to 65°C, the reaction was kept warm for 4 hours, the reaction was completed, naturally cooled, and distilled under reduced pressure to obtain intermediate 1; the ratio of 3,5-di-tert-butyl-4-hydroxybenzaldehyde, piperidine, toluene and melamine was 46.8g:15mL:150mL:14.3g;

[0014] Under the action of the condensing agent, the amino group on melamine condenses with the aldehyde group on 3,5-di-tert-butyl-4-hydroxybenzaldehyde to form an imine group (C=N Schiff base structure), and by controlling the molar ratio of the two to be close to 1:2 and a slight excess of melamine, two amino groups on melamine participate in the reaction to obtain intermediate 1; the specific reaction process is as follows:

[0015]

[0016] S2, add intermediate 1 and N, N-dimethylformamide (DMF) to a three-necked flask equipped with a stirring device, mix, pass nitrogen, add thioglycolic acid and DCC (dicyclohexylcarbodiimide, dehydrating agent) and mix and stir evenly, control the reaction temperature to 55 ° C, keep the reaction for 2 hours, filter after the reaction, first remove part of the solvent by rotary evaporation, and then purify by column chromatography (the eluent is a mixed solvent of benzene / ethyl acetate, the volume ratio of the two is 2:1), remove the eluent by rotary evaporation, and vacuum dry to obtain intermediate 2; the ratio of the amount of intermediate 1, N, N-dimethylformamide, thioglycolic acid, and DCC is 55.8g:150mL:9.1g:20.6g;

[0017] Under the action of a dehydrating agent, the carboxyl group of thioglycolic acid and the amino group of intermediate 1 undergo an amidation reaction, and the reaction can be carried out under relatively mild conditions to obtain intermediate 2. The specific reaction process is as follows:

[0018]

[0019] S3. Mix the nano-samarium oxide with the ethanol aqueous solution, add it to a magnetic stirring device, add a magnet, start stirring, and disperse for 30 minutes to make the nano-samarium oxide evenly dispersed in the ethanol aqueous solution. Vacuum the device and pass N 2 Gas, then vinyl triethoxysilane was added, the reaction temperature was set to 80°C for 4 hours, filtered, washed with ethanol, and then dried in a vacuum drying oven for 2 hours to obtain pre-modified nano samarium oxide; the ratio of nano samarium oxide, ethanol aqueous solution, and vinyl triethoxysilane was 1.0g:100mL:5.5g;

[0020] There are many -OH groups on the surface of nano-samarium oxide. By reacting with vinyl triethoxysilane, carbon-carbon double bond groups can be introduced to obtain pre-modified nano-samarium oxide. The specific reaction process is as follows:

[0021]

[0022] S4, mixing the pre-modified nano samarium oxide with N,N-dimethylformamide, turning on magnetic stirring, stirring for 30 minutes to make the pre-modified nano samarium oxide evenly dispersed, adding AIBN (azobisisobutyronitrile) and intermediate 2, maintaining the temperature of the system at 75°C, reacting for 8 hours, after the reaction is completed, washing with anhydrous ethanol 3-4 times, freeze-drying, grinding, and obtaining modified nano samarium oxide; the ratio of the amount of pre-modified nano samarium oxide, N,N-dimethylformamide, AIBN, and intermediate 2 is 1.0g:100mL:0.1g:12.4g;

[0023] Under the action of AIBN, the unsaturated carbon-carbon double bond on the pre-modified nano-samarium oxide undergoes a thiol-ene click reaction with the thiol group on the intermediate 2 to obtain modified nano-samarium oxide; the structure of the modified nano-samarium oxide is shown below:

[0024]

[0025] As a rare earth element shielding material, nano samarium oxide can effectively absorb X-rays, gamma rays and thermal neutrons due to its special electronic structure. By modifying nano samarium oxide and introducing hydrophobic groups on its surface, the compatibility of nano samarium oxide with polyethylene matrix can be enhanced, and nano samarium oxide can be evenly dispersed in the matrix, so that the performance of nano samarium oxide can be fully exerted, greatly enhancing the shielding performance of the matrix and improving the protection against nuclear radiation. In addition, the modified nano samarium oxide also contains triazine, sulfur, Schiff base and hindered phenol structure. Among them, the triazine structure will produce nitrogen-containing gas during combustion, dilute and reduce the smoke density, self-condense at high temperature to form melem to make the carbon layer compact, which can improve the flame retardant and smoke suppression performance of the matrix; the introduced sulfur element can accelerate the isomerization of the matrix to produce a large amount of CO 2 It also catalyzes the progress of the Fries rearrangement of the matrix and promotes carbonization, further improving the flame retardancy of the matrix; the C=N double bond in the introduced Schiff base structure can generate a carbon-nitrogen six-membered ring at high temperature. This type of six-membered ring structure enables the matrix to form a stable cross-linked network, which synergizes with triazine and sulfur elements to greatly enhance the flame retardancy of the matrix; finally, the hindered phenol structure has excellent antioxidant properties, which can not only improve the antioxidant properties of the matrix, but also act as an antioxidant in the production process, avoiding the addition of additional antioxidants and affecting the homogeneity of the material;

[0026] It should be added that nano-samarium oxide grafted with small organic molecules can prevent the migration and seepage of small organic molecules and improve the durability of performance.

[0027] Beneficial effects of the present invention:

[0028] 1. The polymer material prepared by the present invention uses ultra-high molecular weight polyethylene as a matrix, which gives the material a neutron shielding effect and a certain mechanical strength;

[0029] 2. Adding tungsten boride can further enhance the material's shielding ability against neutrons and also enhance the material's shielding ability against gamma rays;

[0030] 3. By modifying the nano samarium oxide, compared with ordinary nano samarium oxide, it has better compatibility with the polyethylene matrix, can greatly enhance the material's absorption and shielding capabilities for X-rays, gamma rays and neutrons, and can also significantly enhance the material's flame retardancy and oxidation resistance, and the performance is long-lasting and stable and not easy to fall off;

[0031] Therefore, the polymer material prepared by the present invention has high shielding performance, good protection against nuclear radiation, and stable and efficient flame retardant and antioxidant properties, and has important application value in the field of nuclear radiation protection material technology. DETAILED DESCRIPTION

[0032] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Embodiment 1

[0034] Preparation of modified nano-samarium oxide:

[0035] S1. In a three-necked flask equipped with a stirring device, 46.8 g of 3,5-di-tert-butyl-4-hydroxybenzaldehyde, 15 mL of piperidine and 150 mL of toluene were mixed, the temperature was raised to 35° C., and the mixture was stirred until the solid was completely dissolved. 14.3 g of melamine was added, the reaction temperature was controlled to 65° C., and the reaction was kept at this temperature for 4 h. After the reaction was completed, the mixture was naturally cooled and distilled under reduced pressure to obtain intermediate 1.

[0036] S2, in a three-necked flask equipped with a stirring device, add 55.8g of intermediate 1 and 150mL of N,N-dimethylformamide, mix, pass nitrogen, add 9.1g of thioglycolic acid and 20.6g of DCC, mix and stir evenly, control the reaction temperature to 55°C, keep the reaction for 2h, after the reaction is completed, filter, first remove part of the solvent by rotary evaporation, and then purify by column chromatography (the eluent is a mixed solvent of benzene / ethyl acetate, the volume ratio of the two is 2:1), remove the eluent by rotary evaporation, and vacuum dry to obtain intermediate 2;

[0037] S3. Mix 1.0 g of nano-samarium oxide with 100 mL of ethanol aqueous solution, add it to a magnetic stirring device, add a magnet, start stirring, and disperse for 30 minutes to make the nano-samarium oxide evenly dispersed in the ethanol aqueous solution. Vacuum the device and pass N 2 Gas, then add 5.5g of vinyl triethoxysilane, set the reaction temperature to 80℃ for 4h, filter, wash with ethanol, and then dry in a vacuum drying oven for 2h to obtain pre-modified nano samarium oxide;

[0038] S4. Mix 1.0 g of pre-modified nano samarium oxide with 100 mL of N,N-dimethylformamide, turn on magnetic stirring, stir for 30 min to evenly disperse the pre-modified nano samarium oxide, add 0.1 g of AIBN and 12.4 g of intermediate 2, maintain the temperature of the system at 75 ° C, react for 8 h, and after the reaction is completed, wash with anhydrous ethanol 4 times, freeze-dry, and grind to obtain modified nano samarium oxide.

[0039] Embodiment 2

[0040] Preparation of modified nano-samarium oxide:

[0041] S1. In a three-necked flask equipped with a stirring device, 93.6 g of 3,5-di-tert-butyl-4-hydroxybenzaldehyde, 30 mL of piperidine and 300 mL of toluene were mixed, the temperature was raised to 35° C., and the mixture was stirred until the solid was completely dissolved. 28.6 g of melamine was added, the reaction temperature was controlled to 65° C., and the reaction was kept warm for 4 h. After the reaction was completed, the mixture was naturally cooled and distilled under reduced pressure to obtain intermediate 1.

[0042] S2, in a three-necked flask equipped with a stirring device, add 111.6g of intermediate 1 and 300mL of N,N-dimethylformamide, mix, pass nitrogen, add 18.2g of thioglycolic acid and 41.2g of DCC, mix and stir evenly, control the reaction temperature to 55°C, keep the reaction for 2h, after the reaction is completed, filter, first remove part of the solvent by rotary evaporation, and then purify by column chromatography (the eluent is a mixed solvent of benzene / ethyl acetate, the volume ratio of the two is 2:1), remove the eluent by rotary evaporation, and vacuum dry to obtain intermediate 2;

[0043] S3, 2.0g of nano-samarium oxide was mixed with 200mL of ethanol aqueous solution, added to a magnetic stirring device, added a magnet, started stirring, and dispersed for 30min to make the nano-samarium oxide evenly dispersed in the ethanol aqueous solution. The device was evacuated and N 2 Gas, then add 11.0g of vinyl triethoxysilane, set the reaction temperature to 80°C for 4h, filter, wash with ethanol, and then dry in a vacuum drying oven for 2h to obtain pre-modified nano samarium oxide;

[0044] S4. Mix 2.0 g of pre-modified nano samarium oxide with 200 mL of N,N-dimethylformamide, turn on magnetic stirring, stir for 30 min to evenly disperse the pre-modified nano samarium oxide, add 0.2 g of AIBN and 24.8 g of intermediate 2, maintain the temperature of the system at 75 ° C, react for 8 h, and after the reaction is completed, wash with anhydrous ethanol 4 times, freeze-dry, and grind to obtain modified nano samarium oxide.

[0045] Embodiment 3

[0046] 80g of ultra-high molecular weight polyethylene, 15g of modified nano samarium oxide prepared in Example 1, 10g of tungsten boride and 4g of magnesium stearate were added to a mixer and stirred for 30 minutes, then added to a twin-screw extruder, melt blended and extruded to obtain a polymer material with nuclear radiation protection function.

[0047] Embodiment 4

[0048] 90g of ultra-high molecular weight polyethylene, 20g of the modified nano samarium oxide prepared in Example 2, 14g of tungsten boride and 5g of zinc stearate were added to a mixer and stirred for 30 minutes, then added to a twin-screw extruder, melt blended and extruded to obtain a polymer material with nuclear radiation protection function.

[0049] Embodiment 5

[0050] 100 g of ultra-high molecular weight polyethylene, 25 g of modified nano samarium oxide obtained in Example 2, 18 g of tungsten boride and 6 g of paraffin were added to a mixer and stirred for 30 minutes, then added to a twin-screw extruder, melt blended and extruded to obtain a polymer material with nuclear radiation protection function.

[0051] Comparative Example 1

[0052] Ordinary nano samarium oxide of the same mass is used to replace the modified nano samarium oxide in Example 5, and the remaining steps are the same as those in Example 5.

[0053] Comparative Example 2

[0054] Commercially available polyethylene shielding material was used.

[0055] Embodiments 3, 4, 5, and comparative examples 1 and 2 were made into corresponding shapes according to different test standards, and the following performance tests were performed:

[0056] The tensile strength is determined using the national standard GB / T 1040.2-2022 "Determination of tensile properties of plastics";

[0057] The induction time of the sample was determined using the national standard GB / T 19466.6-2009 "Plastics Differential Scanning Calorimetry (DSC) Part 6: Determination of Oxidation Induction Time (Isothermal OIT) and Oxidation Induction Temperature (Dynamic OIT)";

[0058] The national standard GB / T 2406.2-2009 "Determination of Combustion Behavior of Plastics by Oxygen Index Method" was used to measure the oxygen index before and after standing at room temperature for 180 days;

[0059] The measured results are shown in Table 1:

[0060] Table 1

[0061]

[0062] A Cf-252 neutron radiation source was used, and a 12 cm paraffin block was added to moderate the thermal neutron source. A 3He proportional counter imported from LND, USA, was used to measure the thermal neutron attenuation coefficient of the sample.

[0063] The Cf-252 neutron radiation source was used and the 3He counter was used to measure the fast neutron attenuation coefficient.

[0064] Using 60CoY radiation source and NaI crystal detector, the γ radiation attenuation coefficient of the sample was measured;

[0065] The measurement results are shown in Table 2:

[0066] Table 2

[0067]

[0068]

[0069] It can be seen from the above two tables that the polymer material prepared in the embodiment of the present invention has a higher attenuation coefficient for neutrons and gamma radiation than the control example, and its flame retardant and antioxidant properties are also higher than the control example, and its performance is stable, which has important application value in the field of nuclear radiation protection material technology.

[0070] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0071] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A polymer material with nuclear radiation protection function, characterized in that: Prepared by the following steps: Ultra-high molecular weight polyethylene, modified nano samarium oxide, tungsten boride and lubricant are added into a mixer and stirred, and then added into a twin-screw extruder, melt-blended and extruded to obtain a polymer material with nuclear radiation protection function.

2. The polymer material with nuclear radiation protection function according to claim 1, characterized in that: The modified nano samarium oxide is prepared by the following steps: S1. Mix 3,5-di-tert-butyl-4-hydroxybenzaldehyde, piperidine and toluene, heat to 35°C, stir until the solid is completely dissolved, add melamine, keep the temperature at 65°C for 4 hours, and after the reaction is completed, cool naturally and distill under reduced pressure to obtain intermediate 1; S2, mixing intermediate 1 and N,N-dimethylformamide, introducing nitrogen, adding thioglycolic acid and DCC, mixing and stirring evenly, keeping warm at 55°C for 2h, after the reaction is completed, filtering, rotary evaporation, column chromatography purification, rotary evaporation, vacuum drying to obtain intermediate 2; S3, mixing the nano samarium oxide with the ethanol aqueous solution, stirring and dispersing for 30 minutes, evacuating the device, introducing N2 gas, adding vinyl triethoxysilane, reacting at 80°C for 4 hours, filtering, washing, and drying to obtain pre-modified nano samarium oxide; S4. Mix the pre-modified nano samarium oxide with N,N-dimethylformamide, start magnetic stirring, stir for 30 minutes, add AIBN and intermediate 2, react at 75°C for 8 hours, and after the reaction is completed, wash, dry and grind to obtain modified nano samarium oxide.

3. The polymer material with nuclear radiation protection function according to claim 2, characterized in that: In step S1, the ratio of 3,5-di-tert-butyl-4-hydroxybenzaldehyde, piperidine, toluene and melamine is 46.8 g:15 mL:150 mL:14.3 g.

4. The polymer material with nuclear radiation protection function according to claim 2, characterized in that: In step S2, the ratio of the amount of intermediate 1, N,N-dimethylformamide, thioglycolic acid, and DCC is 55.8 g: 150 mL: 9.1 g: 20.6 g.

5. The polymer material with nuclear radiation protection function according to claim 2, characterized in that: In step S3, the ratio of nano samarium oxide, ethanol aqueous solution, and vinyl triethoxysilane is 1.0 g: 100 mL: 5.5 g.

6. The polymer material with nuclear radiation protection function according to claim 2, characterized in that: In step S4, the ratio of the amount of pre-modified nano-samarium oxide, N,N-dimethylformamide, AIBN, and intermediate 2 is 1.0 g: 100 mL: 0.1 g: 12.4 g.

7. The polymer material with nuclear radiation protection function according to claim 1, characterized in that: The raw materials are calculated in parts by weight as follows: 80-100 parts of ultra-high molecular weight polyethylene, 15-25 parts of modified nano samarium oxide, 10-18 parts of tungsten boride, and 4-6 parts of lubricant.